2019
DOI: 10.1111/rssa.12378
|View full text |Cite
|
Sign up to set email alerts
|

Visualization in Bayesian Workflow

Abstract: Bayesian data analysis is about more than just computing a posterior distribution, and Bayesian visualization is about more than trace plots of Markov chains. Practical Bayesian data analysis, like all data analysis, is an iterative process of model building, inference, model checking and evaluation, and model expansion. Visualization is helpful in each of these stages of the Bayesian workflow and it is indispensable when drawing inferences from the types of modern, high dimensional models that are used by app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
686
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 749 publications
(728 citation statements)
references
References 20 publications
(29 reference statements)
3
686
0
3
Order By: Relevance
“…The remaining models were submodels of the first model. Binding potentials were log-transformed because posterior predictive checking 33,34 indicated that log-transformation significantly improves model fit (see Supplementary Figure 2). The log-transformation essentially switches the model from additive to multiplicative; it also helps in model fitting because the assumption of linear additivity works poorly when the dependent variable is restricted to positive values 35 .…”
Section: Model Comparisonmentioning
confidence: 99%
“…The remaining models were submodels of the first model. Binding potentials were log-transformed because posterior predictive checking 33,34 indicated that log-transformation significantly improves model fit (see Supplementary Figure 2). The log-transformation essentially switches the model from additive to multiplicative; it also helps in model fitting because the assumption of linear additivity works poorly when the dependent variable is restricted to positive values 35 .…”
Section: Model Comparisonmentioning
confidence: 99%
“…We tested each random effects standard deviation using the Bayes Factor 10 to further quantify evidence in favor of geographic heterogeneity. SEER-wide and within-state goodness-of-fit was assessed using standard posterior distribution predictive checks 13 (Supporting Information Figs. S1-S8).…”
Section: Methodsmentioning
confidence: 99%
“…This is illustrated with prior-predictive check and assessment of CPM assumptions in Supplemental Material 3, which also shows detailed workflow and visualizations for each observed bacteria. Our prior choice resulted from model comparison with approximate leave-one-out cross-validation 35,36 . Figure 3E shows the corresponding posterior predictive check, suggesting the data is well captured by the modelimplied data generation process for all bacteria.…”
Section: Hierarchical Cpm Predicts Absolute Bacterial Abundancesmentioning
confidence: 99%